1969
DOI: 10.4039/ent101375-4
|View full text |Cite
|
Sign up to set email alerts
|

EFFICACY OF DISULFOTON FOR CONTROL OF THE GREEN PEACH APHID, MYZUS PERSICAE, ON PEPPERS

Abstract: In a 3-year study, one annual application of a 10% granular formulation of disulfoton in the soil at a rate of 2 lb actual toxicant per acre controlled M. persicae throughout the entire period that aphids were most prevalent in pepper fields. Some control was observed within a few days of treatment, but effective control did not occur until 2 to 3 weeks after placement of the insecticide. Irrigation increased the initial uptake of disulfoton, but after 2 weeks the degree of control was essentially the same in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1971
1971
1971
1971

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…. Comparable data from Ridge Farm show similar peaks with generally lower catches in1969 and 1970 (Table I, B). years ( P = 0.05).…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…. Comparable data from Ridge Farm show similar peaks with generally lower catches in1969 and 1970 (Table I, B). years ( P = 0.05).…”
mentioning
confidence: 54%
“…Foott et al (1969) reported a natural decrease in numbers of this aphid on peppers at Harrow at the end of August so that the decline in flights is probably associated with a population decline. Foott et al (1969) reported a natural decrease in numbers of this aphid on peppers at Harrow at the end of August so that the decline in flights is probably associated with a population decline.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Irrigation markedly increased the uptake of disulfoton from granules by cabbage (REYNOLDS and METCALF 1962) et al (1964) in carnations and by RIDcw A Y et al (1965 and in cotton, when deep placement of granules, however, was less effective with irrigation. FOOTT et al ( 1969) examined the control of aphids on peppers with disulfoton granules in the soil and analysed the residues in leaves and fruit, finding increased initial uptake of toxicant in irrigated plots. In England BURT et al (1965) concluded that some systemic insecticide granules in the soil were less effective in dry years than in wet years.…”
Section: D) Soil Watermentioning
confidence: 99%